A study of Coparative Constitutional system with particular reference to doctrine of separation of powers under the Malaysian federal constitution / Muhammad Jauhari Hashim - Hashim, Muhammad Jauhari (Faculty of Law, 1986)
Malaysia with a population of nearly 15 millions is a Federation of thirteen states, headed by His Majesty, the Yang Di Pertuan Agong (hereinafter called the King''. The Federation has 14- legislatives and 14 governments, i .e ; one for the Federation and one for each of the thirteen states. Each of the nine Malay States (which were formerly British profectorates) is headed by a hereditary Sultan and each of the four states (formerly British Colony) by a Governor appointed by the King. The Federation first come into existence in I 896 and in 1946 it was enlarged to embrace all the states (including the two colonies of Malacca and Penang) on the Malay Peninsula, and named the Malayan Union. In 1948 it was renamed the Federation of Malaya with a new constitution. On August 31st, 1957, it was granted independence by the British. In 1963 the Federation was further enlarged and renamed Malaysia.